Blood Coagulation and Beyond: Position Paper from the Fourth Maastricht Consensus Conference on Thrombosis - Akbulut, Asim Cengiz; Arisz, Ryanne A.; Baaten, Constance C. F. M. J.; Baidildinova, Gaukhar; Barakzie, Aarazo; Bauersachs, Rupert; ten Berg, Jur; van den Broek, Wout W. A.; de Boer, H. C.; Bonifay, Amandine; Bröker, Vanessa; Buka, Richard J.; ten Cate, Hugo; ten Cate-Hoek, Arina J.; Cointe, S.; De Luca, Ciro; De Simone, Ilaria; Diaz, Rocio Vacik; Dignat-George, Françoise; Freson, Kathleen; Gazzaniga, Giulia; van Gorp, Eric C. M.; Habibi, Anxhela; Henskens, Yvonne M. C.; Iding, Aaron F. J.; Khan, Abdullah; Koenderink, Gijsje H.; Konkoth, Akhil; Lacroix, Romaric; Lahiri, Trisha; Lam, Wilbur; Lamerton, Rachel E.; Lorusso, Roberto; Luo, Qi; Maas, Coen; McCarty, Owen J. T.; van der Meijden, Paola E. J.; Meijers, Joost C. M.; Mohapatra, Adarsh K.; Nevo, Neta; Robles, Alejandro Pallares; Poncelet, Philippe; Reinhardt, Christoph; Ruf, Wolfram; Saraswat, Ronald; Schönichen, Claudia; Schutgens, Roger; Simioni, Paolo; Spada, Stefano; Spronk, Henri M. H.; Tazhibayeva, Karlygash; Thachil, Jecko; Diaz, Rocio Vacik; Vallier, L.; Veninga, Alicia; Verhamme, Peter; Visser, Chantal; Watson, Steve P.; Wenzel, Philip; Willems, Ruth A. L.; Willers, Anne; Zhang, Pengyu; Zifkos, Konstantinos; van Zonneveld, Anton Jan (Thrombosis and Haemostasis, 2023)
The Fourth Maastricht Consensus Conference on Thrombosis included the following themes. Theme 1: The “coagulome” as a critical driver of cardiovascular disease. Blood coagulation proteins also play divergent roles in biology and pathophysiology, related to specific organs, including brain, heart, bone marrow, and kidney. Four investigators shared their views on these organ-specific topics. Theme 2: Novel mechanisms of thrombosis. Mechanisms linking factor XII to fibrin, including their structural and physical properties, contribute to thrombosis, which is also affected by variation in microbiome status. Virus infection-associated coagulopathies perturb the hemostatic balance resulting in thrombosis and/or bleeding. Theme 3: How to limit bleeding risks: insights from translational studies. This theme included state-of-the-art methodology for exploring the contribution of genetic determinants of a bleeding diathesis; determination of polymorphisms in genes that control the rate of metabolism by the liver of P2Y12 inhibitors, to improve safety of antithrombotic therapy. Novel reversal agents for direct oral anticoagulants are discussed. Theme 4: Hemostasis in extracorporeal systems: the value and limitations of ex vivo models. Perfusion flow chamber and nanotechnology developments are developed for studying bleeding and thrombosis tendencies. Vascularized organoids are utilized for disease modeling and drug development studies. Strategies for tackling extracorporeal membrane oxygenation-associated coagulopathy are discussed. Theme 5: Clinical dilemmas in thrombosis and antithrombotic management. Plenary presentations addressed controversial areas, i.e., thrombophilia testing, thrombosis risk assessment in hemophilia, novel antiplatelet strategies, and clinically tested factor XI(a) inhibitors, both possibly with reduced bleeding risk. Finally, COVID-19-associated coagulopathy is revisited.
Keywords: antiplatelet agent; artificial surfaces; atherosclerosis; oral anticoagulants; thrombosis